Are markets adaptive? Evidence of predictability and market efficiency of lodging/resort REITs - Almudhaf, Fahad; Aroul, Ramya Rajajagadeesan; Hansz, J. Andrew (International Journal of Strategic Property Management, 2020)
We investigate the degree of return predictability of lodging/resort real estate investment trusts (REITs) from January 1994 to May 2016. We test the Martingale hypothesis by using linear (automatic portmanteau and automatic variance ratio with rolling windows) and nonlinear tests (generalized spectral shape tests and Dominguez-Lobato consistent tests). Our findings support the Adaptive Market Hypothesis (AMH) and reveal that returns experience periods of both dependence and independence. We document time-varying predictability of lodging/resort REITs with returns as both initially predictable and subsequently unpredictable throughout the majority of the period of analysis. Moreover, we find that if traders use simple technical trading moving average rules, they can capitalize on the inefficiencies of lodging/resort REITs. Finally, we observe that absolute returns and Sharpe ratios of technical moving average rules outperform a simple buy-and-hold strategy.